The Rise and Fall of Spain's 'Nuclear Exceptionalism' - PORTELA, Clara (Institutional Knowledge at Singapore Management University, 2014)
The present article looks at the evolution of Spanish views on deterrence and non-proliferation. Like every member state of the North Atlantic Treaty Organisation (NATO), Spain is covered by the US nuclear umbrella and has accepted the logic of deterrence, while at the same time maintaining a denuclearised status and committing to the goal of disarmament enshrined in the non-proliferation treaty. This article explores the background of Spain's apparently contradictory situation as a denuclearised member of NATO and how it positions itself in regard to the nuclear question in the current security context. It concludes that while Spanish nuclear ‘exceptionalism’ originally rested on the reluctance of the political elites to alter the precarious compromise that once allowed for Spain's accession to NATO as a denuclearised member, it gradually withered away to give way to a close alignment with Alliance policies driven by a desire to preserve strong security links with its partners.